PENERAPAN ACTIVE LEARNING DENGAN STRATEGI ROTATING TRIO EXCHANGE PADA MATERI SISTEM PERNAPASAN - ANDRIANTO, AVIF (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2012)
Abstract — Based on observation’s result in class XI IPA 1 SMA Negeri 4 Sidoarjo on August 2011 during 2nd Teaching Experience Program, it is known that students become inactive over the time. To overcome this problem, it requires learning model that can make students remain active in learning activities called active learning. This research aims to describe rotating trio exchange students’ activities, describe students’ learning outcomes, and students’ response. The type of this study is pre-experimental research while the applied-reserach design is one shot case study. The research’s subject is students of class XI IPA 1 at SMA Negeri 4 Sidoarjo. The obtained data were analyzed using descriptive quantitative analysis. The results showed that: (1) the application of rotating trio exhange strategy improved students’ learning outcomes, (2) frequently students’ activity on each meeting is discussing in groups of three, (3) student learning outcomes showed mixed results, and (4) students’ response is very positive. Key words: Learning Application, Active Learning, Rotating Trio Exchange Strategist, Respiratory System  Matter.